GROWTH PERFORMANCE AND ECONOMIC APPRAISAL OF PHASE FEEDING AT DIFFERENT STOCKING DENSITIES IN SEXED BROILERS - S. Mehmood; A.W. Sahota; M. Akram; K. Javed; J. Hussain; M.S. Shaheen; Y. Abbas; A. S. Jatoi; A. Iqbal (Journal of Animal and Plant Sciences, 2014)
The present study was undertaken to examine the growth performance and economic efficiency involving 1440 sexed broilers (720 of each sex), maintained in environmentally controlled broiler house under litter floor subjected to four different levels of phase-feeding at three different stocking densities (0.7, 0.6, 0.5 sq.ft). The birds in group- A were offered diet with 19% crude protein (CP) throughout the grow-out period of 42 days. Those in group-B were allotted broiler starter diet with 20% CP up to 28 days of age and then broiler finisher diet with 17% CP up to 42 days of age. The diet for birds in group-C was split into 03 phases i.e. 0-10, 11-26, 27-42 days furnishing with 21, 19 and 18 % CP, respectively. The birds in group D were maintained on 4 phase feeding regimes i.e. 0-10, 11-20, 21-34, 35-42 days, with CP levels of 21, 20, 18 and 17%, respectively. Weekly data on growth performance parameters were recorded and were analyzed using Completely Randomized Nested Design. The comparison of means was made using DMR test. The results revealed that birds maintained at 0.7 sq. ft. stocking density exhibited significantly (P<0.05) better body weight, FCR, uniformity, point spread and point index, while, significantly highest feed intake, body weight and improved FCR was recorded in 4-phase feeding program as compared to single, two and three phase feeding pattern but sex did not significantly influence these parameters. Higher profit was achieved in four phase feeding program at 0.7 sq. ft. stocking density.
Keywords: broiler; sex; phase feeding; stocking density; growth performance; economics